Structural problems of the next few years - Dieter Schröder (Intereconomics, 1976)
The Federal Republic of Germany will be facing in the next few years changes in its economic structure which, if not in their extent, in their effect on the employment situation will be without parallel in the post-war period. After fifteen years of nearly uninterrupted full employment, it is reasonable to expect in the medium term an over-all rate of unemployment of the order of 2–3 p.c. (0.5–0.7 mn).
Keywords: 330; Germany